Explicating the Comprehension Skills Based on the Strategies on the Instruction of the Core Subjects of Junior High School Students - Salomon, Elizabeth (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between teachers’ instructional strategies and the comprehension skills of junior high school students in English, Mathematics, and Science, with the goal of providing an empirical basis for the development of an enhanced self-learning module. Anchored on cognitive, socio-cultural, sequential, and learning theories, the study employed a descriptive-correlational research design. Quantitative data were gathered using two researcher-developed survey questionnaires administered to junior high school students and teachers in Minglanilla District II. Descriptive statistics were used to determine respondent profiles, the extent of strategy utilization, and levels of student comprehension, while robust regression analysis was applied to examine relationships between instructional strategies and comprehension skills. Results showed that teachers in all three subjects demonstrated a high extent of instructional strategy utilization, particularly cooperative learning, practice exercise sessions, and structured activities. However, students’ comprehension skills varied across subjects, with English at a low level and Mathematics and Science at moderate levels. Regression analysis revealed significant positive relationships between instructional strategies and comprehension skills in English and Mathematics, with cooperative learning emerging as the strongest predictor, while results in science were mixed, indicating that effectiveness depends on appropriate implementation and contextual alignment. The study identified language proficiency, resource allocation, and student motivation as key barriers to effective learning. The findings support Sustainable Development Goal 4 (Quality Education) by emphasizing effective instructional practices that improve learning outcomes and contribute to educational sustainability through informed curriculum enhancement and teacher professional development.
Keywords: Comprehension Skills; Instructional Strategies; Junior High School Students; Mathematics Education; Science Education; Self-Learning Module; Teaching Effectiveness